Fabrication of high-concentration Cu-doped deuterated targets for fast ignition experiments - Ikeda T; Kaneyasu Y; Hosokawa H; Shigemori K; Norimastu T; Cadatal-Raduban M; Nagai K; Kojima S; Abe Y; Miura E; Kitagawa Y; Takemura M; et al. (IOP Publishing Ltd on behalf of the International Atomic Energy Agency (IAEA), 2023)
In high-energy-density physics, including inertial fusion energy using high-power lasers, doping tracer atoms and deuteration of target materials play an important role in diagnosis. For example, a low-concentration Cu dopant acts as an x-ray source for electron temperature detection while a deuterium dopant acts as a neutron source for fusion reaction detection. However, the simultaneous achievement of Cu doping, a deuterated polymer, mechanical toughness and chemical robustness during the fabrication process is not so simple. In this study, we report the successful fabrication of a Cu-doped deuterated target. The obtained samples were characterized by inductively coupled plasma optical emission spectrometry, differential scanning calorimetry and Fourier transform infrared spectroscopy. Simultaneous measurements of Cu K-shell x-ray emission and beam fusion neutrons were demonstrated using a petawatt laser at Osaka University.
Keywords: fast ignition experiments; laser target; neutron detection; x-ray tracer